2017
DOI: 10.1016/j.jhep.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

How viral genetic variants and genotypes influence disease and treatment outcome of chronic hepatitis B. Time for an individualised approach?

Abstract: Chronic hepatitis B virus (HBV) infection remains a global problem. Several HBV genotypes exist with different biology and geographical prevalence. Whilst the future aim of HBV treatment remains viral eradication, current treatment strategies aim to suppress the virus and prevent the progression of liver disease. Current strategies also involve identification of patients for treatment, namely those at risk of progressive liver disease. Identification of HBV genotype, HBV mutants and other predictive factors al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
127
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 218 publications
(224 reference statements)
11
127
0
8
Order By: Relevance
“…In our study, 465 patients with HBeAg‐negative chronic HBV were analysed including a high percentage of HBV genotype A and D infected patients, but also a significant number of patients with HBV genotype B, C and E. Mutations in PC, BCP and preS were found in a genotype‐dependent pattern, which has been described for BCP and PC mutations among genotypes A‐D and for preS mutations among genotypes B and C, respectively . As no data are published regarding the prevalence of these mutations in HBV genotype E, we found that the vast majority of GTE‐infected patients harboured the BCP double mutation. While preS mutations were also commonly found, mutations in precore were detected only infrequently in this genotype.…”
Section: Discussionmentioning
confidence: 62%
“…In our study, 465 patients with HBeAg‐negative chronic HBV were analysed including a high percentage of HBV genotype A and D infected patients, but also a significant number of patients with HBV genotype B, C and E. Mutations in PC, BCP and preS were found in a genotype‐dependent pattern, which has been described for BCP and PC mutations among genotypes A‐D and for preS mutations among genotypes B and C, respectively . As no data are published regarding the prevalence of these mutations in HBV genotype E, we found that the vast majority of GTE‐infected patients harboured the BCP double mutation. While preS mutations were also commonly found, mutations in precore were detected only infrequently in this genotype.…”
Section: Discussionmentioning
confidence: 62%
“…However, the major limitation is that the heterogeneity of the patient characteristics is inevitable in this multi‐centre study, although HBV DNA, HBV serological markers and noninvasive markers (PIIINP, MMP‐1, Hp, HA, sCD163 and α2‐MG) were measured at the central laboratory, and liver histological examination was performed by special hepatopathologists, and the upper limit of normal (ULN) of ALT and AST was determined according to the detection method used in each institute. In addition, HBV genotype, which influences disease course and treatment outcomes of CHB, 54 was not investigated in our cohort. Studies have confirmed no statistically significant differences between HBV genotype and virological responses to nucleos(t)ide analogue therapies 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBV genotype, which influences disease course and treatment outcomes of CHB, 54 was not investigated in our cohort. Studies have confirmed no statistically significant differences between HBV genotype and virological responses to nucleos(t)ide analogue therapies 54 . Given the fact that the complex interaction mechanism between HBV and host immunity has not been thoroughly studied, the current research results are limited to Asians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been exemplified by the management of hepatitis C virus infection (5), and a similar approach for HBV is starting to emerge, with recent EASL guidelines for HBV treatment suggesting different stopping points for treatment non-response in genotypes A-D (6). Evidence increasingly supports a role for HBV genotype in influencing disease progression including risk of developing chronic infection, e-antigen seroconversion, transmission mode, and the development of hepatocellular carcinoma (7,8). Studies often refer to ‘wild-type’ virus (8,9), but ‘wild-type’ for one genotype may not reflect consensus for other genotypes (10,11).…”
Section: Introductionmentioning
confidence: 99%